2009
DOI: 10.1111/j.1439-0531.2007.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Refrigerated Storage of Red Deer Epididymal Spermatozoa in the Epididymis, Diluted and with Vitamin C Supplementation

Abstract: We have approached the problem of refrigerated storage of epididymal sperm samples from red deer by comparing three options: storing the genital (testicles within the scrotum), diluting the semen in extender or diluting the semen in extender supplemented with an anti-oxidant. Twenty-nine pairs of testes were collected. Spermatozoa from one of each of the pairs were immediately recovered, and diluted to 400 x 10(6) sperm/ml in Tris-citrate-fructose with 20% egg yolk. Control group was stored as such, and Anti-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 56 publications
(100 reference statements)
3
16
0
Order By: Relevance
“…Correlation between RFM and storage time was -0.54±0.18. Similar data were obtained in studies of low-temperature postmortal storage of epididymides of mice [12], sheep [11], deer [8,9], dogs [15], and feline species [6,10]. These studies revealed a negative effect of postmortal storage of the epididymides on RFM of native and frozen-thawed spermatozoa.…”
Section: Effects Of Cooling and Storage Time Of The Mouse Carcass At supporting
confidence: 82%
“…Correlation between RFM and storage time was -0.54±0.18. Similar data were obtained in studies of low-temperature postmortal storage of epididymides of mice [12], sheep [11], deer [8,9], dogs [15], and feline species [6,10]. These studies revealed a negative effect of postmortal storage of the epididymides on RFM of native and frozen-thawed spermatozoa.…”
Section: Effects Of Cooling and Storage Time Of The Mouse Carcass At supporting
confidence: 82%
“…In addition, cold storage for 24 hr did not affect the Siamese Eld's deer epididymal sperm motility and membrane and DNA integrity in the present study. This finding was in accordance with the studies in sika and red deer [3,4] and domestic cats [2]. During 24-hr of cold storage, anti-oxidative mechanism in the sperm cells might neutralize lipid peroxidation, a cause of sperm damage, as was shown in the horse [7].…”
supporting
confidence: 91%
“…One of the most commonly reported is sperm processing, especially centrifugation and incubation (Bungum et al 2008;Koderle et al 2009;Matsuura et al 2010). Another potential factor is the use of different types of extenders (Shahiduzzaman and Linde-Forsberg 2007;Fernandez-Santos et al 2009;Morrell et al 2009). The purpose of short-term preservation of dog sperm is to maintain fertilization potential for a longer time than is the case for fresh semen.…”
mentioning
confidence: 99%